Implementasi Pemasaran Digital dengan AI dalam Upaya Meningkatkan Penjualan UMKM Soto Batok dan Roti Bakar - Gagas Pratasona; Yudas Tadius Adi Chandra (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2024)
Based on the results of interviews with business actors of Soto Batok and Roti Bakar Bandung in Agromulyo village, Sedayu district, Bantul regency, Yogyakarta. That business actors have not been optimal in conducting digital marketing, this community service aims to increase knowledge to important business actors in digital marketing in an effort to increase sales. The methods used are counseling, interviews, training and mentoring. Business actors can gain new knowledge about marketing and how to implement digital marketing in their businesses. The researcher conducts training and assistance to businesses in implementing digital marketing, such as training on making effective copywriting, and how to take good product photos, as well as how to make interesting posts on social media. Training and mentoring will be carried out during October 2024. And the participating business actors gave a good response. New business actors understand the importance of implementing digital marketing and how to implement it effectively.